Pelaksanaan program perlindungan sosial di Malaysia / Suhaimi Abd Samad - Suhaimi , Abd Samad (2018)
This study aims to see the implementation of social protection programs in Malaysia by focusing on the issue of implementation of the policy with reference to a number of factors such as 1) the policy and program, 2) organizations implementing the policies, 3), policy implementing agency and 4) environmental factors; as introduced by O'Toole theory through Multiactor Policy Implementation. This theory is also based on the previous early theories of implementation such as Top-Down and Bottom-Up. It is undeniable that the studies in this field have been actively conducted by previous researchers, but after a few decades, new variables have emerged in the implementation of the programs, especially in terms of social protection. This study involves the program under the scope of public assistance provided by the Department of Social Welfare and the Ministry of Rural and Regional Development. A total of eight (8) implementers and seven (7) beneficiaries of public assistance programs in Malacca and Penang were chosen as respondents in order to obtain information on implementation of such programs by the two providers of public assistance. The findings from interviews has been further strengthened by triangulation method through document review and observation during the coordination meeting and delivery of public assistance session. The result of the research has shown that, based on recent developments and current evolution, several factors and a new phenomenon has emerged and have an impact on the implementation of social protection program. Among the significant new variables are the need for database, enforcement of rules and regulations, and implementers freedom from intervention, uniformity, politicking, the role of local authorities, media, audit and as well as attitude of the beneficiaries themselves. This study has been able to fill the next gap in the theory of policy implementation by streamlining the Multiactor theory and previous other implementation theories.